Zasp regulates integrin activation - Bouaouina, Mohamed (The Company of Biologists, 2012)
Integrins are heterodimeric adhesion receptors that link the extracellular matrix (ECM) to the cytoskeleton. Binding of the scaffold protein, talin, to the cytoplasmic tail of β-integrin causes a conformational change of the extracellular domains of the integrin heterodimer, thus allowing high-affinity binding of ECM ligands. This essential process is called integrin activation. Here we report that the Z-band alternatively spliced PDZ-motif-containing protein (Zasp) cooperates with talin to activate α5β1 integrins in mammalian tissue culture and αPS2βPS integrins in Drosophila. Zasp is a PDZ–LIM-domain-containing protein mutated in human cardiomyopathies previously thought to function primarily in assembly and maintenance of the muscle contractile machinery. Notably, Zasp is the first protein shown to co-activate α5β1 integrins with talin and appears to do so in a manner distinct from known αIIbβ3 integrin co-activators.